2007
DOI: 10.1152/ajprenal.00278.2006
|View full text |Cite
|
Sign up to set email alerts
|

A role for AMP-activated protein kinase in diabetes-induced renal hypertrophy

Abstract: We tested the hypothesis that AMP-activated protein kinase (AMPK), an energy sensor, regulates diabetes-induced renal hypertrophy. In kidney glomerular epithelial cells, high glucose (30 mM), but not equimolar mannitol, stimulated de novo protein synthesis and induced hypertrophy in association with increased phosphorylation of eukaryotic initiation factor 4E binding protein 1 and decreased phosphorylation of eukaryotic elongation factor 2, regulatory events in mRNA translation. These high-glucose-induced chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
287
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(306 citation statements)
references
References 67 publications
15
287
0
1
Order By: Relevance
“…AICAR did not affect the total number of renal macrophages in the mouse model used, but rather shifted their phenotype towards resolution by reducing the percentage of CD11c + M1 macrophages. Collectively, this supports previous work from our group and others, demonstrating that AICAR attenuates both HFD-induced [12,13] and diabetes-induced [14,15] kidney disease. Importantly, in this study, we now also demonstrate that AICAR-mediated protection against kidney disease is independent of adiponectin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…AICAR did not affect the total number of renal macrophages in the mouse model used, but rather shifted their phenotype towards resolution by reducing the percentage of CD11c + M1 macrophages. Collectively, this supports previous work from our group and others, demonstrating that AICAR attenuates both HFD-induced [12,13] and diabetes-induced [14,15] kidney disease. Importantly, in this study, we now also demonstrate that AICAR-mediated protection against kidney disease is independent of adiponectin.…”
Section: Discussionsupporting
confidence: 91%
“…Evidence from experimental models has shown that AICAR may attenuate metabolic [6][7][8], hepatic [9][10][11] and renal pathophysiology [12][13][14][15]. However, the use of AICAR could be compromised as some reports indicate that AICAR increases adiponectin production [13].…”
Section: Introductionmentioning
confidence: 99%
“…Restriction of energy intake augments insulin-stimulated PI3K activity in response to a physiological insulin concentration (60 μU/ml) [29]. In contrast, at the supraphysiological concentration of insulin, such as in db/db (more than 200 μU/ml) mice, PI3K would be activated in the kidney [44].…”
Section: Discussionmentioning
confidence: 99%
“…20 Briefly, 10-week-old anesthetized mice were injected retroorbitally with dialyzed 5% fluorescein isothiocyanate-inulin. Blood was collected from the tail at 3,5,7,10,15,35,56, and 75 minutes after injection. Separated serum was buffered in 0.5 mol/L HEPES, pH 7.4, and fluorescence was measured as described previously.…”
Section: Measurement Of Glomerular Filtration Ratementioning
confidence: 99%
“…3e9 Among KLF proteins, KLF2 is a key regulator of vascular hemodynamic forces in vivo 10 and mediates flowdependent phenotype in endothelial cells. 3,11 KLF2 has been shown to be essential in maintenance of endothelial integrity in adult mice 12 as well as in mouse embryonic vasculature.…”
mentioning
confidence: 99%